Developing a bi-objective model of the closed-loop supply chain network with green supplier selection and disassembly of products: The impact of parts reliability and product greenness on the recovery network. (July 2015) - Ghayebloo, Sima; Tarokh, Mohammad Jafar; Venkatadri, Uday; Diallo, Claver
Highlights: A bi-objective MILP model is used to study trade-offs between greenness and profit. Pareto-optimal solutions generated by the ε-constraint method show the trade-offs. Sensitivity analysis done to help the decision maker in selecting key parameters. Experiments depicts interactions between flow of parts, reliability and greenness. Abstract: Closed-loop supply chain network (CLSCN) design aims to incorporate environmental considerations into the traditional supply chain design by including recycling, disassembly and reuse activities. A CLSCN incorporates the use and reuse of environmentally friendly products and materials supported by the design of an appropriate recovery, disassembly, and refurbishing network. In the design process, a trade-off must often be made between the need to maximize profit and maximize greenness. The latter is considered for several reasons including regulatory requirements, corporate responsibility and corporate image. In this paper, a bi-objective mixed integer programming model is developed and solved for a forward/reverse logistic network including three echelons in the forward direction (suppliers, assembly centers and customer zones) and two echelons in the reverse direction (disassembly and recycling center). A set of Pareto optimal solutions is obtained to show the trade-off between the profit and the greenness objectives. Some useful managerial insights are developed through various computational experiments.